The Changing Place of Developing Countries in Global Economy - Marinov, Eduard (Economy and Business Yearbook, 2022)
The article analyzes the increasing demand and the formation of internal value chains in developing countries - changes that explain the shift in the intensity and direction of trade at the global level. The aim of the study is to analyze the new place of developing countries in global trade relations. First, some of the transformations in the positions of the countries of the Global South in the process of multilateral liberalization are considered, then the changing role of emerging economies in the world economy is analyzed, and finally a forecast on the changing global demand and trade patterns is presented.